A study of the association between identity, life engagement and well-being among young Asian adults - Berezina, E *; Gill, C. M. H. D.*; Bovina, I. (Routledge, 2020)
The eudaemonic tradition asserts that life engagement, that is the pursuit of a meaningful way of living, is an important element of well-being. Self-identity theory posits that individuals’ identities significantly contribute to their sense of meaning and belonging, which in turn boost well-being. The present study aimed to establish the extent to which self-identities are predictors of wellbeing and whether they are subsumed within the life engagement construct. An opportunity sample of Singaporeans (n = 269) aged 18–35 (M = 23.88, SD = 4.52) completed the Aspects of Identity Questionnaire, Warwick-Edinburgh Mental Well-Being Scale and Life Engagement Test. Correlational analysis showed that personal, social, relational and collective identities were significantly associated with life engagement and well-being. However, multiple regressions demonstrated that life-engagement subsumed collective and relational identity almost completely, and also accounted for a significant amount of the variance in personal and social identities in the prediction of well-being, broadly supporting the eudaemonic model. It was shown that social and personal identities were predictors of well-being beyond life engagement, possibly because these identities satisfy some of psychological needs that promote various benefits that are independent of life engagement, yet still important for wellbeing. It is suggested that these differences in the salience of identity types to well-being may be indicative of changes in the sense of identity among young Singaporeans that have arisen as a result of social policy or possibly changes in the ways of identity expression in the Internet. The implications of the findings are discussed and recommendations made for future research.